Outpatient Bryant's Overhead Traction Does Not Affect the Rate of Open Reduction or Avascular Necrosis in Developmental Dislocation of the Hip. Issue 3 (30th March 2022) - Elerson, Emily E.; Martin, Benjamin D.; Muchow, Ryan D.; Pierce, William A.; Jo, Chan-Hee; Hinds, Sean A.; Birch, John G.
Abstract : Background: The efficacy of preliminary traction to increase the likelihood of closed reduction and/or decrease the incidence of avascular necrosis in the management of developmental dysplasia of the hip (DDH) is controversial. We sought to document compliance with and effectiveness of Bryant's outpatient traction in patients with idiopathic DDH. Methods: Patients presenting between 6 and 24 months of age with idiopathic irreducible DDH were prospectively enrolled in the study. Prereduction outpatient traction was prescribed at participating surgeons' preference and parents' expressed willingness to comply with a traction protocol of at least 14 hours/day for 4 weeks. Traction hours were documented using a validated monitor; parents also reported average daily usage. Rate of successful closed reduction and evidence of capital epiphyseal growth disturbance 1 year' and 2 years' postreduction were documented. Results: Ninety-six patients with 115 affected hips were enrolled. Reliable recorded traction hours were obtained in 31 patients with 36 affected hips. Defining compliance as 14 hours/day average use, 14 of 31 patients (45.2%) were compliant, 2 (6.5%) admitted noncompliance, while 15 (48.2%) claimed to be compliant, but were not. Overall, 68/115 hips (59.0%) were closed reduced. Age at treatment was the only demographic characteristic associated with an increased incidence of closed reduction (11.7 vs. 14.6 mo, P <0.01). Successful closed reduction was achieved in 10/16 hips (62.5%) of compliant patients, 12/20 (60.0%) of noncompliant patients, and 43/72 (59.7%) of no-traction patients. Irregular ossific nucleus development was noted 1-year postindex reduction in 5/16 (31.3%) of complaint-patient hips and 25/92 (27.2%) of noncomplaint and no-traction hips. Distorted proximal femoral epiphysis was noted at 2 years postreduction in 2/15 hips (13.3%) of compliant patients and 15/52 hips (28.8%) in noncompliant and no-traction patients. None of these differences was statistically significant. Conclusions: Parent-reported use of outpatient traction is unreliable. Four weeks of outpatient overhead Bryant's traction did not affect the rate of closed reduction or avascular necrosis in late-presenting DDH in this cohort. Level of Evidence: Level II—prospective cohort.